2022
DOI: 10.1016/j.idh.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Australian dentists’ knowledge, preparedness, and experiences during the COVID-19 pandemic

Abstract: Background COVID-19 is a global health crisis. Close contact with the mucous membranes and respiratory secretions of patients and aerosol-generating procedures renders dentists and other oral health professionals at high risk of exposure to SARS-CoV-2. We examined dentists’ knowledge, preparedness, and experiences of managing COVID-19 in Australia. Methods A cross-sectional online survey of dentists with a current membership with The Australian Dental Association (ADA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
7
0
2
Order By: Relevance
“…This study also describes US dentists' concerns for how COVID-19 may exacerbate oral health disparities in low socioeconomic groups and among older adults with comorbidities. In addition, this study's qualitative findings contribute valuable narratives to the previous survey studies of dentists' experiences during COVID-19 around the world, articulating topics including anxiety, provider preparedness, and increased stress among practitioners [9][10][11][12].…”
Section: Discussionmentioning
confidence: 84%
“…This study also describes US dentists' concerns for how COVID-19 may exacerbate oral health disparities in low socioeconomic groups and among older adults with comorbidities. In addition, this study's qualitative findings contribute valuable narratives to the previous survey studies of dentists' experiences during COVID-19 around the world, articulating topics including anxiety, provider preparedness, and increased stress among practitioners [9][10][11][12].…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, social media influencers can be hired to inform and influence the DHCPs, especially the students and interns. In addition, video resources that provide comprehensive information on the infection control procedures and sequences could be developed, similar to those developed by the Australian dental association, to demonstrate the donning and doffing sequences of the PPE [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study [ 35 ], a Polish study [ 36 ], and a German study [ 37 ] also evaluated knowledge scores among dentists. All the studies found sufficient knowledge regarding COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf et al [ 37 ] survey reported that COVID-19 changed the dental practice drastically. Subsequently, an Australian study reported that [ 35 ] holistic training is mandatory for successfully managing patients in the dental operatory during the COVID-19 outbreak. It has also been reported that many changes were evident in the dental operator, and it is also time to adopt the new strategies and inflectional protocols in the dental operatory [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%